Term Viable Abdominal Pregnancy- A Case Report - Yasmin, N; Daise, TA; Begum, MH; Sultana, J (Medicine Today, 2013)
A lady of 24 years was presented with the complains of 40 weeks pregnancy and abdominal pain for 3 days. Her abdominal examination revealed that abdomen was tense, tender,uterine contour could not be ascertained. A lining foetus of transverse lie was felt in the upper part of abdomen. Liquor was seems to be insufficient. Her USG findings was term pregnancy, oligohydramnions,transvers lie with central placenta previa. Her laperatomy finding was intact shiny amniotic sac was present at the upper part of abdomen, uterus was 12 weeks size and was in normal position that is within the pelvic cavity. Lie of the foetus was transverse,placenta was found to be implanted on the fundus of uterus. Baby was delivered by breech extraction. Subtotal hysterectomy was done due to profuse uncontrolled bleeding from placental implantation site. Her post operative period was uneventful and recovery was good. She was discharged on 8th post operative day. DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15015 Medicine Today 2012 Vol.24(2): 85-86